2020
DOI: 10.3389/fcell.2020.00625
|View full text |Cite
|
Sign up to set email alerts
|

The Dysregulation and Prognostic Analysis of STRIPAK Complex Across Cancers

Abstract: The striatin-interacting phosphatase and kinase (STRIPAK) is the highly conserved complex, which gains increased attention in physiology and pathology process recently. However, limited studies reported the details of STRIPAK complex in cancers while some results strongly suggested it plays a vital role in tumorigenesis. Hence, we systematically analyzed the molecular and survival profiles of 18 STRIPAK genes to assess the value of STRIPAK complex across cancers. Our findings revealed the low frequencies of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The dysregulated expression of metastasisassociated genes has been linked to the initiation, progression and prognosis of NSCLC [39] . In addition, STRIPAK complexes have shown to play an important role in cell growth, differentiation, proliferation and apoptosis of metabolism, immune regulation and tumor metastasis [11] . However, the current understanding of the function and possible mechanism of STRIP2 (STRIPAK major component) in NSCLC tumorigenesis is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulated expression of metastasisassociated genes has been linked to the initiation, progression and prognosis of NSCLC [39] . In addition, STRIPAK complexes have shown to play an important role in cell growth, differentiation, proliferation and apoptosis of metabolism, immune regulation and tumor metastasis [11] . However, the current understanding of the function and possible mechanism of STRIP2 (STRIPAK major component) in NSCLC tumorigenesis is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that the STRIPAK genes were aberrantly expressed and served as a prognostic value in various cancer, such as STRN4 [40] , STRN3 [12] , STRIP1 [12,41] , STRIP2 [12,16] , MST4 [42] , MOB4 [42] , SLMAP [11] , PPP2R1A [11] , PDCD10 [11] and CTTNBP2NL [11] . In the present study, survival analysis using Kaplan-Meier Plotter online datasets revealed that patients with high STRIP2 expression had a poorer prognosis compared with those with low STRIP2 expression, suggesting that STRIP2 could be considered as a prognostic marker for NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different combinations of these core proteins and accessory proteins results in the formation of different STRIPAK complexes. And it was reported that the STRIPAK complex plays many important roles in embryo development, cancer, diabetes, autism, and many other diseases, and regulates many important signaling pathways and cellular processes ( Hwang and Pallas, 2014 ; Wong et al, 2014 ; Zhang et al, 2014 ; Lant et al, 2015 ; Madsen et al, 2015 ; Sakuma et al, 2015 , 2016 ; Bazzi et al, 2017 ; Chursa et al, 2017 ; Huang et al, 2017 ; Pal et al, 2017 ; Zheng et al, 2017 ; Elramli et al, 2019 ; Kuck et al, 2019 ; Tang et al, 2019 ; Rodriguez-Cupello et al, 2020 ; Seo et al, 2020 ; Stein et al, 2020 ; Xie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The STRIPAK complex, an evolutionarily conserved supramolecular complex, is involved in many important physiological processes and diseases, including embryogenesis and development ( Lant et al, 2015 ; Sakuma et al, 2015 , 2016 ; Bazzi et al, 2017 ; Pal et al, 2017 ; Zheng et al, 2017 ), type 2 diabetes ( Chursa et al, 2017 ), and cancer progression ( Wong et al, 2014 ; Zhang et al, 2014 ; Madsen et al, 2015 ; Huang et al, 2017 ; Rodriguez-Cupello et al, 2020 ). The STRIPAK complex has several different formations depending on the combinations of different, mutually exclusive accessory proteins to the STRIPAK core components ( Hwang and Pallas, 2014 ; Kuck et al, 2019 ; Rodriguez-Cupello et al, 2020 ; Seo et al, 2020 ; Stein et al, 2020 ; Xie et al, 2020 ). Several important proteins combine to form the core STRIPAK components, including a striatin family member, the PP2A A/C heterodimer, Mob3, Strip1 or Strip2, and a GCKIII kinase bound via Ccm3 ( Goudreault et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other major components of STRIPAK complexes contain striatin-interacting protein 1 or 2 (STRIP1 or STRIP2, also named as family with sequence similarity 40 (FAM40) A or B), the MOB family member 4 protein (MOB4), the cerebral cavernous malformation 3 protein (CCM3), and the germinal center kinase III (GCKIII) family kinase (MST3, MST4, or STK25) [9,10]. Recently, STRIPAK complexes show many physiological and pathological functions, and dysregulation of STRIPAK components is participated in cancer [11]. Previous study has shown that STRIPAK components FAM40A, FAM40B, and STRN3 determine the model of cancer cell migration and metastasis through regulating the contractile cytoskeleton phenotype [12].…”
mentioning
confidence: 99%